2000
DOI: 10.1634/theoncologist.5-2004-45
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Vascular Endothelial Growth Factor Blockade: Ascites and Pleural Effusion Formation

Abstract: Primary Purpose. Formation of ascites and pleural effusion (PE) is a common problem for patients with advanced-stage cancer. These fluid accumulations cause severe symptoms such as abdominal distention, shortness of breath, cachexia, anorexia, and fatigue. Preclinical models have demonstrated that vascular endothelial growth factor (VEGF) plays a pivotal role in the accumulation of malignant PE or ascites. This study investigated whether blockade of VEGF activity would reduce biological activity of PE and asci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 5 publications
1
32
0
Order By: Relevance
“…The altered expression of VEGF-A has been reported to be associated with the poor prognosis of various types of human cancer (13,14). Multiple clinical studies have also demonstrated the potential benefit of VEGF-A inhibition in patients with malignant effusions (15). Anti-angiogenic therapy (such as bevacizumab, a monoclonal antibody targeting VEGF-A) adjuvant to chemotherapy serves a potential function in the management of pleural effusions in advanced non-squamous non-small cell lung cancer (5,16).…”
Section: Introductionmentioning
confidence: 99%
“…The altered expression of VEGF-A has been reported to be associated with the poor prognosis of various types of human cancer (13,14). Multiple clinical studies have also demonstrated the potential benefit of VEGF-A inhibition in patients with malignant effusions (15). Anti-angiogenic therapy (such as bevacizumab, a monoclonal antibody targeting VEGF-A) adjuvant to chemotherapy serves a potential function in the management of pleural effusions in advanced non-squamous non-small cell lung cancer (5,16).…”
Section: Introductionmentioning
confidence: 99%
“…Because ascites fluid contains many cells of tumor origin in addition to other soluble growth factors that have been associated with invasion and metastasis (11,12), this fluid contains the secretome of ovarian cancer cells while reflecting other microenvironmental factors of the malignancy. Thus, applying the ever advancing technique of proteomics analysis on ascites, it may be possible to discover novel biomarkers that are more sensitive and specific than those currently available.…”
mentioning
confidence: 99%
“…Highly efficient anti-tumor effects were observed in HOZOT-treated mice which demonstrated almost complete eradication of inoculated WiDr cells in the peritoneal cavity and no accumulation of tumor ascites. In clinical oncology of cancers at advanced stages, especially the advanced stage caused by aggressive carcinomas mainly from digestive organs, it is important to manage cancer cell dissemination in the peritoneal/thoracic cavity and to reduce the accumulation of tumor ascites (18,19). Taking these issues into consideration, our results emphasize the promising clinical utility of HOZOT against advanced stage colon cancer.…”
Section: Discussionmentioning
confidence: 69%